Halal Industry Potential In West Nusa Tenggara: Strengthening Islamic Economics in The Global Market - Basit, Abdul; Sakti, Reza Arviciena; Zahari, Yudhi Kurniawan; Knight, Oliver William; Prayuda, I Putu Septian Adi (Likuid Jurnal Ekonomi Industri Halal, 2025)
This study employs a qualitative approach with a descriptive method to analyze the potential for halal industry development in West Nusa Tenggara Province as a strategy to enhance Islamic economic competitiveness. In this context, clear and supportive regulations are essential to create a conducive environment for the development of the halal industry. The objective of this study is to assess the potential for halal industry growth in West Nusa Tenggara Province as a driver for increasing Islamic economic competitiveness amid global market dynamics.  Secondary data was collected from various sources, including official reports from local governments, policies related to the halal industry, scientific publications, and reports from research institutions focusing on Islamic economics and the halal industry. This study relies on both primary and secondary data to ensure comprehensive analysis. The findings highlight the importance of government policies and collaborative efforts to stimulate the growth of the halal industry, such as regulatory frameworks, financial incentives, and institutional support.